Under (implicit) pressure: young Black and Latina women's perceptions of contraceptive care - Gomez, Anu Manchikanti; Wapman, Mikaela (Contraception (Stoneham), 2017)
To understand the ways in which young women of color experienced pressure from healthcare providers during contraceptive care, including the impact of these encounters on contraceptive decision making and reproductive autonomy. Data were drawn from a qualitative study of contraceptive decision making, which included 38 young (age 18–24) Latina and Black women recruited using community-based and online strategies. We analyzed in-depth interview data from a subsample of 27 young women who described experiencing pressure from healthcare providers during contraceptive care. We conducted a thematic analysis of coded data using a cross-case analytic approach. Our analysis revealed that the pressure experienced by our participants was typically subtle and constrained reproductive autonomy to varying degrees. We termed this phenomenon implicit pressure owing to the under-the-surface nature of these experiences — that is, participants perceived an implied outcome regarding contraceptive use favored by their providers. Participants felt implicitly pressured when providers appeared to prefer certain methods based on imbalanced provision of information, tone of voice and affect, and minimization of or failure to describe potential side effects. Some participants accepted their providers' contraceptive suggestions as a way to end counseling encounters — methods they rapidly discontinued. Experiences of implicit pressure were longitudinally impactful, with some participants curtailing future healthcare access and contraceptive use because of negative clinical encounters. Practices that implicitly pressure women in contraceptive counseling can infringe upon reproductive autonomy and reinforce health inequities when they engender mistrust of healthcare, providers and contraception. This study underscores the importance of high-quality contraceptive care for young women of color. Adverse healthcare experiences during adolescence and young adulthood can negatively impact future health-seeking behavior, with important implications for health throughout the life course. Patient-centered approaches may positively affect patients' experiences while continuing to facilitate contraceptive discussions.